NON-LINEAR SECTIONAL ANALYSIS OF CONCRETE ENCASED STEEL STUB COLUMN SUBJECTED TO AXIAL LOAD - Tugas Hutomo Putra; Bambang Piscesa; Hidajat Sugihardjo (Institut Teknologi Sepuluh Nopember, 2023)
This paper presents a numerical parametric study of Concrete Encased Steel Column (CESC) due to centrically and eccentrically axial load. To model the confining pressure of rebar and steel profile, modified Mander’s equations was used. The non-linear sectional analysis was performed using an in-house NL-Column program using the fiber-based method. The CESC section was discretized using Netgen 2D meshing algorithm. The developed CESC model was validated using the available test results in the literature. After model was validated, parametric studies were carried out to investigate the behaviors of CESC with different concrete compression strength, confinement bar diameter, and confining space. The parametric studies found that the column with higher concrete compression strength tend to have higher axial and flexural capacity but reduce the overall ductility. Increasing the confinement bar diameter slightly increases the axial and flexural capacity and ductility on the other hand, utilizing tighter confinement space resulted in higher ductility but with small increase in axial and flexural capacity.